ENFORCEMENT AGAINST MISUSE OF DEEPFAKE TECHNOLOGY FOR PORNOGRAPHY ON SOCIAL MEDIA - Ery Susanti; Tahasak Sahay; Rizki Setyobowo Sangalang; Indang Sulastri (RADJA PUBLIKA, 2026)
deepfake technology , which is being misused for pornographic content on social media. This study aims to analyze law enforcement and its obstacles in the Cyber Crimes Directorate of the Central Kalimantan Regional Police. The method used is empirical legal research with a qualitative descriptive approach through interviews and literature review. The results show that law enforcement is carried out through stages of inquiry, investigation, and prosecution, referring to the ITE Law, the Pornography Law, and the Criminal Code, and supported by preventive efforts such as digital literacy and cyber patrols. However, its implementation has not been effective due to obstacles in digital evidence, limited forensic facilities, and difficulties in identifying anonymous perpetrators across regions. Therefore, strengthening specific regulations, improving digital forensic facilities, and increasing the capacity of law enforcement officers is necessary.